Implementing virtual reference services : a LITA guide - Thomsett-Scott, Beth C. (LITA guides, 2013)
Social web technologies present an often confusing array of options for answering user reference questions. Applying 20 years' experience as a reference librarian working through the development of virtual reference and the integration of new tools and technologies into the industry, Thomsett-Scott lays out how libraries are using vendor services such as LibraryH3lp, LibAnswers, and Text a Librarian, as well as free tools like Twitter and Google Voice for their reference needs. Practitioners offer details on virtual reference services such as Twitter Search, instant messaging services such as.